Importancia de la implementación de sistema de posicionamiento global (GPS) en la agricultura de precisión - Moyano Morán, Jairo Hipólito (2025)
The implementation of modern technologies, such as the Global Positioning System, has been a key solution, specifically in the execution of precision agriculture. Technology has proven its effectiveness as we face today's modern problems of irrigation, scarce resources as well as climate impact. Instruments such as remote sensors, smart irrigation systems and GPS are in the role of providing farmers with the greatest information necessary to make correct decisions that would contribute to the improvement of their operation and activity, as well as the results. GPS, among other things, changed the way resources are determined and managed to plant and harvest crops more accurately, avoiding unnecessary damage, optimizing land use, and improving the use of inputs such as water. After these investigations and experiences with these technologies, it was only shown that they increase productivity and promote a more sustainable and environmentally responsible activity; however, we still have an important challenge to face. Adoption and recognition of these existing tools, especially in remote areas of the agricultural chain, are important. Therefore, it is important to exploit and develop new solutions so that more farmers can enjoy them and build more efficient resources for food production.